DOACROSS Parallelization Based on Component Annotation and Loop-Carried Probability - Mattos, Luis; Cesar, Divino; Salamanca, Juan; Carvalho, João P. L. de; Pereira, Marcio; Araujo, Guido (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2018)
Although modern compilers implement many loop parallelization techniques, their application is typically restricted to loops that have no loop-carried dependences (DOALL) or that contain well-known structured dependence patterns (e.g. reduction). These restrictions preclude the parallelization of many computational intensive DOACROSS loops. In such loops, either the compiler finds at least one loop-carried dependence or it cannot prove, at compile-time, that the loop is free of such dependences, even though they might never show-up at runtime. In any case, most compilers end-up not parallelizing DOACROSS loops. This paper brings three contributions to address this problem. First, it integrates three algorithms (TLS, DOAX, and BDX) into a simple openMP clause that enables the programmer to select the best algorithm for a given loop. Second, it proposes an annotation approach to separate the sequential components of a loop, thus exposing other components to parallelization. Finally, it shows that loop-carried probability is an effective metric to decide when to use TLS or other non-speculative techniques (e.g. DOAX or BDX) to parallelize DOACROSS loops. Experimental results reveal that, for certain loops, slow-downs can be transformed in 2× speed-ups by quickly selecting the appropriate algorithm.